Comparative analysis of company performance result financial statements - Stončiuvienė, Neringa; Zinkevičienė, Danutė (Buhalterinės apskaitos teorija ir praktika, 2014)
In the scientific literature there are researches presenting the comparison of the form of financial statements of business and public sector and non-profit organizations, however in Lithuania these issues have not been performed. Cross-cultural differences in national accounting and reporting create preconditions for a more detailed research in Lithuania. All this presupposes the need to evaluate pros and cons of different organizations, provides to look for commonalities between different sectorial reports. Proposals for presentation alignment of results of corporate and public sector and non-profit organizations are encountered in the literature, as well as proposals for application of different reporting formats. Detailed analysis of accounting and presentation of performance results in financial statements of business and public sector and non-profit organizations was carried out in this research. At first, it showed that all organizations prepare their performance reports on an accrual basis. The reports contain information both on results of organization's operating activity, and on financial and investment activities. Only the business organizations present information about special items. However, specifics of activities and aim to meet the different information needs of users determine that it is not appropriate to align the organization's performance reports.
Keywords: performance result; profit; loss; business; public sector; non-profit organizations